the Study of some pro- inflammatory and Anti –inflammatory interleukins in diabetic patients - saad, enaas; Adnan, Dhuha; Alwan, Mohammed (ASJ - Academic Science Journal, 2024)
Objective; The objective  of present   research is evaluation roles of IL-38 and IL-39  indicators in pathophysiology  of diabetic mellitus type II.Methods; The conducted investigation  was occurred inside Bagdad capital during time  period   1/8 to 30/11 month  of  2023 year. Forty five (45) blood samples had from patients suffering from type II diabetes that attending outpatients clinics after screening  them by specialist  physician . Additionally, 45 blood samples were collected from individuals without disease  and considered them as control group. All markers were quantified   in all participants  by utilize enzyme linked immunesorbent assay (ELISA) with kits provided  from Bio-Sources International (Camarillo, CA, USA). Results of current investigation were calculated by  SPSS v. 21.0 and Prism v.6 statistical software  programs.Results; Findings of current investigation  showed no significant differences (p>0.05) between study groups according to gender and age groups. Significant raise (p251.21 and > 182.29) respectively in predicting individuals  with diabetes mellitus type II  with significant variation (p0.05) between levels of IL-38 and IL-39 and gender as well as to age groups in patients with diabetes. Finally, pearson correlation coefficient results reveals no significant correlation (P>0.05) between IL-38 and IL-39 in diabetes patients .Conclusions; We concluded there is no effect of gender and age on diabetes mellitus. Increased levels of pro and anti-inflammatory interleukins (IL-39 and IL-38) in patients due to inflammation. Anti-inflammatory interleukin (IL-38) increased due to effect of pro- inflammatory interleukin (IL-39) to reducing the intensity of inflammatory reactions and preserving physiological equilibrium in essential organs. IL-38 is highly preferred in predicting diabetic patients than IL-39 due to it has highest sensitivity and specificity. There  is no effect of gender and age on levels of these interleukins in DM patients. Finally, it is founded there is no significant correlation between IL-38 and IL-39 in those patients.